La gestión del riesgo en la industria forestal uruguaya - Soledad Nión; Francisco Pucci; Fiorella Ciapessoni (Universidade do Porto, 2013)
The paper examines three Uruguayan forest companies of wood and paper pulp sector with high capital investment, whose work processes have been modernized and achieved a relative improvement in working conditions. However, it still remains patterns of production and recruitment that come in strong contradiction with those changes. The outsourcing of work processes is associated with the presence of forms of hiring by productivity, which reproduces the conditions in which the physical burden of the day and the competition to achieve the performances required by the companies, exacerbate the difficulties in establishing efficient politics of risk management.